Efficiency of 128-bit Encryption and Decryption Process in Elgamal Method Using Elliptic Curve Cryptography (ECC) - Dicky Nofriansyah; Afzalur Syaref; Widiarti R Maya; Ganefri Ganefri; Ridwan Ridwan (Universitas Ahmad Dahlan, 2018)
Cryptography is a growing science of data security. The integrity of a data is an important thing to keep the secrets contained in the data. In this research will be visualized the efficient quantities that use elliptic curves and do not use them. The Elgamal method is an asymmetric cryptographic algorithm whose complexity of processes. It is especially for digital signatures. This research will discuss about the use of ECC to optimize and streamline the Encryption and Decryption process in particular 128-bit Elgamal method. The hope is that by using elliptic curves the timing of the encryption and decryption process can run faster in the computation of Elgamal Method.